Epigenetic regulation of stem cells in lung cancer oncogenesis and therapy resistance - Wu, Jiayang; Feng, Jiaming; Zhang, Qiran; He, Yazhou; Xu, Chuan; Wang, Chengdi; Li, Weimin (Frontiers in Genetics, 2023)
Epigenetics plays an important role in regulating stem cell signaling, as well as in the oncogenesis of lung cancer and therapeutic resistance. Determining how to employ these systems to treat cancer is an intriguing medical challenge. Lung cancer is caused by aberrant signals that cause aberrant differentiation of stem cells or progenitor cells. The pathological subtypes of lung cancer are determined by the cells of various origins. Additionally, emerging studies have demonstrated that the occurrence of cancer treatment resistance is connected to the hijacking of normal stem cell capabilities by lung cancer stem cells, especially in the processes of drug transport, DNA damage repair, and niche protection. In this review, we summarize the principles of the epigenetic regulation of stem cell signaling in relation to the emergence of lung cancer and resistance to therapy. Furthermore, several investigations have shown that the tumor immune microenvironment in lung cancer affects these regulatory pathways. In the final section, we list some ongoing epigenetics-related therapeutic strategies with the aim of developing subsequent epigenetic and lung cancer stem cell-based therapies.